Info
この質問は閉じられています。 編集または回答するには再度開いてください。
My answer is not matching with attached file
1 回表示 (過去 30 日間)
古いコメントを表示
syms k r
a=sym('a'); b = sym('b');L=sym('L'); M = sym('M'); b1 = sym('b1');
m=7; F = sym(zeros(m,1)); F(1)=0; F(2)=1; F(3)=a;
G = sym(zeros(m,1)); G(1)=0; G(2)=1/2; G(3)=b;
for k=1:7
for r = 1:k
F3 = F(1)+ F(2)+F(3); G3 = G(1)+G(2)+G(3);
F(k+3)= ( F3+sum((r+1)*F(r+1)*(k-r+1)*F(k-r+1)) - sum((k-r+1)*(k-r+2)*F(k-r+1)*(F(r)+G(r)))+ (M+L)*(k)*F(k+1))/((1+b1)*(k+1)*(k+2)*(k));
G(k+3) = (G3+ sum((r+1)*G(r+1)*(k-r+1)*G(k-r+1)) - sum((k-r+1)*(k-r+2)*G(k-r+2)*(F(r)+G(r))) + (M+L)*(k)*G(k+1))/((1+b1)*(k+1)*(k+2)*(k));
end
end
% %%%%%
for N=1:6
disp(F(N))
disp(G(N))
end
f=sum(x^k*F(k),k,0,7)
g=sum(x^k*G(k),k,0,7)
%%%%%%%
Any reply will be greatly appreciated
After getting F(N) and G(N), I neeed to find then f and g
8 件のコメント
Walter Roberson
2020 年 1 月 14 日
You have not posted the recurrence formula, so we are restricted to pointing out parts of the code that look suspicious, without being able to make any suggestions as to what code would work.
回答 (0 件)
この質問は閉じられています。
参考
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!